STUDI ALIRAN 3-D NEAR ENDWALL PADA INTERAKSI AIRFOIL DAN PLAT DATAR - Rachman, Arfidian; Yuana Dewi, Arfita; Effendi, Asnal (ITP Press, 2024)
Studies of the existence of these secondary flow structures are based on the effect of the emergence of secondary flows in the wing-body configuration on aircraft, i.e. the presence of wingtip-vortex on the tip region and the creation of several elements of the vortex flow on the endwall region, both of which together will cause the blockage of the main flow. The existence of this blockage effect will affect the aerodynamic characteristics of the lift and drag, where it directly affects the effectiveness and efficiency of the wing. In the endwall area the phenomenon can be observed is the shift of the position of the saddle point towards the pressure side. Whereas from the isobar contour the movement of the minimum pressure point on the upper surface is found to be closer to the leading edge, and the area of maximum pressure on the lower surface moves towards the press side. The research will be conducted experimentally on a wing geometry variation modeled on a flat plate with an angle of attack variation (α) = 0o.